Energy Transition and its Societal Challenges. Themes, Gaps and Possible Developments in Sociology - Monaco, Salvatore (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2021)
The issue of the energy transition, that can be defined as the transition from the use of fossil fuels (in particular coal) to low-carbon energy resources (such as wind, solar and natural gas), is assuming an increasingly central importance in the public debateand has increasingly become the focus of public concern. Scientifically speaking, the challenge and goal of achieving pursuing a more sustainable and fairer low-carbon energy sector globally has encouraged the proliferation of a series of scientific contributions, in various fields of knowledge. The paper shows the results of a literature review on the topic of energy transition. The review takes into consideration a selection of papers taken from international scientific journals with the aim of mapping at a broader level the research on the topic and the issues that were mainly addressed in the years between 2015 and 2020. With the more specific aim of understanding the role of sociology in the international scientific debate on the energy transition, the paper aims to provide an overview of 1) research fields and disciplines; 2) places of publication; 3) research topics and questions.